A lightweight privacy and integrity preserving range query scheme for mobile cloud computing. Issue 84 (July 2019) - Xu, Zhou; Lin, Yaping; Arthur Sandor, Voundi Koe; Huang, Zhisheng; Liu, Xinbo
Abstract: Mobile cloud computing has received a particular attention in recent years thanks to the expansion and easy accessibility of smartphones with enhanced capabilities, pushing for data owners to outsource more data to the cloud in order to serve the increasing number of mobile users. To protect data privacy, data have to be encrypted prior to outsourcing. Nevertheless, mobile users should still be able to query data, get the results corresponding to their requests and verify the integrity of the query results, all within a query privacy-preserving and efficient fashion. We focus in this work on the secure range query allowing to search for data belonging to a specific range. At the difference of previous works where data privacy and query results verification require separate structures and thus more overhead, our work achieves both data privacy and query results completeness verification using the encrypted data index and the vector neighbor chain (VNC). As a response to the intrinsic limitations of mobile devices, we design a lightweight protocol based on linear algebra operations for both 1-dimensional and multi-dimensional data. Practical experiments analysis on a real-world U.S. Census demographic dataset shows that our scheme guarantees the privacy-preserving property and is efficient in terms of computation and communication overhead.